Retrospective study of patients' persistence on treatment with vitamin K antagonists in the setting of an anticoagulation clinic in Italy. Issue 2 (August 2015) - Fiorelli, Elisa M.; Ricci, Silvia; Birocchi, Simone; Carpani, Giovanni; Cattaneo, Marco
Highlights Low persistence on vitamin K antagonists (VKA) increases the thromboembolic risk Persistence on VKA at an anticoagulation clinic in 2013 was retrospectively checked 64 of 483 patients did not attend the first visit at the anticoagulation clinic 23.9% of 419 patients prematurely discontinued their regular follow-up visits Discontinuation of VKA appeared unjustified in 8.8% of patients